Pemberdayaan Masyarakat Pesisir melalui Pengelolaan Sistem Tipologi Desa untuk Pencapaian SDGs di Kecamatan Pagimana Kabupaten Banggai - Jafar Lantowa (Univeristas Negeri Gorontalo, 2022)
The complex socio-economic conditions of the community have an influence on the typology system of the coastal community village of Kec. Pagimana. From social systems such as diverse social status and lack of social relations because there are many immigrants so that familiarity has not created an attitude of togetherness to move forward, and furthermore the cultural system is still mixing local culture due to urbanization factors which have an impact on the erosion of the culture of the local coastal community. This problem will be an obstacle in achieving the SDGs so that special attention needs to be paid in dealing with these problems. The purpose of implementing this Village Development Community Service Program is to provide program assistance to coastal communities related to the management of the village typology system for the achievement of SDGs in Pagimana District, Banggai Regency. Thus, the target and output of this service activity is the existence of SDGs village typology data that can be used in formulating village activity program planning and in a sustainable manner the village community is educated and trained in economic development as a village business based on the advantages of the village. Besides that, the outputs are also documentation of reports and articles as well as videos of the KKNT implementation process. The service program through the Thematic KKN Gorontalo State University in 2021 in Toipan Village, Kec. Pagimana, Kab. Banggai has 5 core programs including; computer training, making boundaries, socializing about the environment, socializing HIV/AIDS and Public Speaking, while the program in Pisou Village, Pagimana District, Proud Regency, namely the launching of Perdana WASERDA (Warung Serba Ada), Training on Making Papaya Fruits into Papaya Sticks and Introduction to Tools and Materials Coffee for MSMEs, and Introduction and Training of Google Forms for Village Officials.